Analisis Pengaruh Pemanfaatan Teknologi PendidikanTerhadap Konsentrasi Belajar Siswa Kelas 3 SDN 13/I Muara Bulian - Mia Apta Candra; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the influence of educational technology utilization on the learning concentration of third-grade students at SDN 13/I Muara Bulian. The use of educational technology such as laptops, projectors, and educational games has increasingly been implemented to create more interactive and engaging learning environments. This research employed a qualitative descriptive method. Data were collected through classroom observations, in-depth interviews with classroom teachers and students, and documentation of learning activities. The results of the study indicate that the utilization of educational technology has a positive influence on students’ learning concentration. The use of laptops and projectors helps students focus on learning materials through visual and audiovisual presentations, while educational games encourage active participation and sustained attention during learning activities. These findings demonstrate that well-planned and guided educational technology can effectively improve students’ learning concentration. Therefore, the study concludes that the integration of laptops, projectors, and educational games in classroom learning contributes positively to enhancing students’ learning concentration at the elementary school level.